THE ROLE OF CULTURAL-LINGUISTIC INTUITION AND REFLECTIVE LEARNING IN DEVELOPING COMPENSATORY COMPETENCE OF LINGUISTIC UNIVERSITY STUDENTS - Tojieva Gavhar Yakubovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article examines how cultural-linguistic intuition and reflective learning develop compensatory competence in first-year EFL students. Intuition is presented not only as grammatical sensitivity but also as an emotionally and culturally grounded ability, working alongside reflection to help learners manage linguistic gaps. Drawing from the Uzbek educational context, the article underscores challenges such as limited language exposure and proposes strategies like peer collaboration, context-rich input, and visual support. It integrates insights from key scholars to advocate for interdisciplinary, strategic approaches to language learning.